Red lists of threatened species—Indicators with the potential to act as strategic circuit breakers between science and policy. Issue 113 (November 2020) - Rabaud, Suzanne; Coreau, Audrey; Mermet, Laurent
Highlights: Many operators and academics in the field of environmental science stress the key role played by indicators at the interface between science and policy. We put a priority focus on the perspective and action situations of the operators who design and use the indicators to promote better biodiversity outcomes. We replace those tools in the context of the wider strategy of these operators in favour of biodiversity. Through the exemple of red lists of threatened species, we show that indicators with the potential to connect and disconnect science and policy are the most useful ones, strategically. The double-edge purpose of indicators, at the same time informative and evaluative, enables operators to lean towards the informative, or towards the evaluative, following strategic intent. Abstract: Although thousands of biodiversity indicators have already been designed, scientists and decision-makers are still asking for new versions. Why are we still not satisfied? Our argument is that, if biodiversity indicators aim to improve the effectiveness of science-policy interfaces, it is essential to assess their actual contribution to biodiversity conservation. How? Through an analysis of current uses of indicators in the strategic interactions among a set of actors placed in a given field of biodiversity organized actions This paper presents our investigations into the use of French national and regional red lists of threatened species as a strategic resource for scientists and policy-makers. The manner the red lists are designed, discussed and used is essential so that they can be adapted to suit the way biodiversity is managed in France. The lists systematise information on threatened species in ways that allow users to strategically connect or disconnect knowledge and action, according to the needs of environmental operators in different situations. Their contribution to effective biodiversity actions lies in what we call their potential to act as 'circuit breakers' between science and policy. This research suggests new perspectives both for analysing environmental management situations including indicator design and for operators who want to design new indicators.